Effects of Ginsenoside Biopolymer Nanoparticles on the Malignant Behavior of Non-Small-Cell Lung Cancer - Weizheng Zhou; Chengliang Cai; Hui Shi; Hai Jin; Xiaowei Wang (Advances in Polymer Technology)
Objective. To explore the effects and mechanism of ginsenoside Rg3 nanoparticles on the malignant behavior of non-small-cell lung cancer. Methods. The nanoparticle carriers were prepared by using an electrostatic system, and the coverage of ginsenoside Rg3 was determined by HPLC after coating the nanoparticle carriers with the ginsenoside Rg3 monomer. The proliferation of H125 cells was measured using MTT assay, and the Transwell assay was used to detect the invasiveness of H125 cells. Cell scratch test was used to determine the migration ability of H125 cells, and Western blotting was used to measure the expression level of PTEN in H125 cells; the expression level of miR-192 in H125 cells was measured via RT-qPCR, and the apoptosis level of H125 cells was detected by Tunel assay. Results. Firstly, gelatin nanoparticles and hyaluronic acid nanoparticles were uniformly distributed, uniform in size and spherical in shape, and after coating ginsenoside Rg3, the sizes of the nanoparticles were significantly increased. Secondly, the expression level of miR-192 was upregulated in H125 cells, which could be effectively inhibited by the treatment of Rg3 monomer and HA-Rg3 nanoparticles. Thirdly, the knockdown of miR-192 significantly inhibited H125 cell proliferation, invasion, and migration and also enhanced H125 cell apoptosis. In addition, PTEN was demonstrated as a target gene of miR-192. Finally, by inhibiting the expression level of miR-192 in H125 cells, the Rg3 monomer and HA-Rg3 nanoparticles upregulated the expression of PTEN and thus exerted its antitumor effect; the effects of HA-Rg3 were comparatively more significant than those of the Rg3 monomer. Conclusions. The Rg3 monomer and HA-Rg3 nanoparticles mitigated the malignant behavior of human non-small-cell lung cancer H125 cells through the miR-192/PTEN molecular axis, and HA-Rg3 nanoparticles showed better antitumor effects.